EVALUATION OF THE TIME AND EFFICIENCY OF TRUNATOMY, VDW.ROTATE, PROTAPER GOLD AND RECIPROC BLUE IN SHAPING ROOT CANALS - AN IN VITRO STUDY - Adina-Bianca Piț; Ioana-Amalia Borcean; Ionela-Andreea Vărgatu; Andreea Mai; Maryam Shyblak; Samir Mokdad; Laura-Elena Cîrligeriu; Luminița-Maria Nica (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study To analyse and compare on extracted teeth the shaping time and the modifications of the root canal contour by using four different nickel-titanium mechanical systems. Material and methods Four groups, each of 6 human single-rooted teeth, were shaped using TruNatomy (Dentsply Sirona Maillefer), VDW.ROTATE (VDW), ProTaper Gold (Dentsply Sirona) or Reciproc blue 25 (VDW) and the shaping time was digitally recorded. Initial and final cone beam computed tomography (CBCT) images were taken and the same cross-section of each sample was analyzed in Image J program to measure the initial area of the root canal, before shaping, and the final area, after the use of each system. Differences between final and initial area were calculated and a statistical analysis was performed. Results The amount of tooth structure removed was minimum for VDW.ROTATE and TruNatomy, as expected. Also, TruNatomy recorded the shortest shaping time, with a mean of 14.05s/canal, significantly different from all the other systems. Conclusions Nickel-titanium shaping systems with reduced taper and fewer instruments are more conservative and efficient in root canal shaping.